1998
DOI: 10.1177/104973239800800606
|View full text |Cite
|
Sign up to set email alerts
|

A Spiritual Response to the Challenge of Routinization: A Dialogue of Discourses in a Buddhist-Initiated Hospice

Abstract: The hospice vision of providing democratic and humane care of the dying needs to be operationalized in the "real world" of health care bureaucracies. It is at this interface between idealists and the demands of mainstream health care that hospice organizations experience compromise, diversion, and an ongoing threat to their singleness of purpose. This discussion explores this process of routinization through research findings on a hospice organization known as Karuna Hospice Service (KHS). Such findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Current views emphasize that encounters take place over time and involve the patient, the family, and the medical team [11]. The potential value of an ongoing relationship is suggested by our finding that time to death is associated with increasing clarity of understanding, which may also grant the opportunity to discuss religious and spiritual issues as well as medical and health matters [30]. Timmermans [21], Mamo [22], and Valdimarsdottir et al [15] all found that the process of developing an awareness of dying is a gradual one for family caregivers.…”
Section: Discussionmentioning
confidence: 76%
“…Current views emphasize that encounters take place over time and involve the patient, the family, and the medical team [11]. The potential value of an ongoing relationship is suggested by our finding that time to death is associated with increasing clarity of understanding, which may also grant the opportunity to discuss religious and spiritual issues as well as medical and health matters [30]. Timmermans [21], Mamo [22], and Valdimarsdottir et al [15] all found that the process of developing an awareness of dying is a gradual one for family caregivers.…”
Section: Discussionmentioning
confidence: 76%
“…Such a spiritual discourse was found to be actively creating and supporting both the discursive space for holistic care of the dying and a subjectivity for a compassionate and tolerant hospice worker. Not only was the KHS way of "speaking the world" seen to attract and support individuals who sanction a loving, caring and gentle way of relating to each other and the families they work with, it also informed a client subjectivity based on a psychosocial-spiritual interpretation of their needs (McGrath, 1996;1997a;1997b;1998a;1998b).…”
Section: Discourse Examples Of Another "Way" -Khs's "Talk" On Chmentioning
confidence: 98%
“…The early work of James and Field called attention to a concern about the counter-productive dimension of the bureaucratic pressure inherent in regular use of instrumentations [12]. The move towards routine incorporation of standardized assessment tools is seen as a negative outcome of the process of routinization, a process by which the compassionate, holistic ideology of the hospice movement is undermined by the increasing bureaucratic pressure to 'measure' and 'quantify' [12,20]. The challenge for hospice and palliative care organizations is seen to be one of maintaining adherence to the core values of humane patient-and family-centred care, in the face of the pressure towards routinization and bureaucratization [20,21,35].…”
Section: Introductionmentioning
confidence: 99%
“…The move towards routine incorporation of standardized assessment tools is seen as a negative outcome of the process of routinization, a process by which the compassionate, holistic ideology of the hospice movement is undermined by the increasing bureaucratic pressure to 'measure' and 'quantify' [12,20]. The challenge for hospice and palliative care organizations is seen to be one of maintaining adherence to the core values of humane patient-and family-centred care, in the face of the pressure towards routinization and bureaucratization [20,21,35]. This is difficult at a time when hospices need to demonstrate the use of standardized tools for accreditation purposes, and are increasingly forced to justify their activity in terms of measurable and cost-efficient outcomes [21].…”
Section: Introductionmentioning
confidence: 99%